PEDIATRIC OXYGEN THERAPY: A CLINICAL UPDATE - Haque, Anwarul; Rizvi, Munaza; Arif, Fehmina (Journal of Ayub Medical College Abbottabad, 2016)
Oxygen therapy is a life-saving, medical intervention in the management of hospitalized children. The goal of oxygen therapy is to prevent or treat tissue hypoxia. Oxygen should be prescribed according to the principles of drug prescription, however, use of oxygen in clinical practice is often inappropriate without knowledge of its potential risks and benefits. This article summarizes practical aspects of clinical use of oxygen in terms of indication, administration, and monitoring, weaning, discontinuation and oxygen toxicity to rationalize therapy and achieve maximum benefits. Keywords: Oxygen, administration, device, children